2015
DOI: 10.1021/acs.accounts.5b00472
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Metabolic Activation Biomarkers of Carcinogenic Tobacco-Specific Nitrosamines

Abstract: Conspectus Lung cancer is the leading cause of cancer death in the world, and cigarette smoking is its main cause. Oral cavity cancer is another debilitating and often fatal cancer closely linked to tobacco product use. While great strides have been made in decreasing tobacco use in the United States and some other countries, there are still an estimated 1 billion men and 250 million women in the world who are cigarette smokers and there are hundreds of millions of smokeless tobacco users, all at risk for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 50 publications
1
106
0
Order By: Relevance
“…28 The NNN and NNK compounds are also known to form haemoglobin adducts in humans as well as in experimental animals. 29,30 The use of toombak, which has high NNN and NNK levels as mentioned above, has been associated with cancers of the oral cavity. 31,32 Many factors may influence the uptake or absorption of TSNAs in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…28 The NNN and NNK compounds are also known to form haemoglobin adducts in humans as well as in experimental animals. 29,30 The use of toombak, which has high NNN and NNK levels as mentioned above, has been associated with cancers of the oral cavity. 31,32 Many factors may influence the uptake or absorption of TSNAs in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Under strong acid hydrolysis conditions, the majority of POB-DNA adducts decompose to release 4-hydroxy-1-(3-pyridyl)-1-butanone (HPB) [4143]. In vitro and laboratory animal studies have demonstrated the importance of HPB-releasing adducts in NNK- and NNN-induced carcinogenesis [32,44]. Earlier, we described the enhanced carcinogenicity of (S)-NNN compared to (R)-NNN.…”
Section: Tobacco Carcinogensmentioning
confidence: 99%
“…2 NNK is metabolized to 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL, 2 , Figure 1), which is also a potent lung carcinogen with activity similar to NNK. 1,3,4 Both NNK and NNAL are metabolically activated by α-hydroxylation catalyzed by cytochrome P450s to form a series of intermediates which react with DNA to form adducts. The formation of these DNA adducts can cause miscoding and mutations in growth control genes, 57 which is a critical step in carcinogenesis by NNK and NNAL.…”
Section: Introductionmentioning
confidence: 99%